2014
DOI: 10.3390/coatings4020214
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bias Voltage and Gas Pressure on the Structure, Adhesion and Wear Behavior of Diamond Like Carbon (DLC) Coatings With Si Interlayers

Abstract: Abstract:In this study diamond like carbon (DLC) coatings with Si interlayers were deposited on 316L stainless steel with varying gas pressure and substrate bias voltage using plasma enhanced chemical vapor deposition (PECVD) technology. Coating and interlayer thickness values were determined using X-ray photoelectron spectroscopy (XPS) which also revealed the presence of a gradient layer at the coating substrate interface. Coatings were evaluated in terms of the hardness, elastic modulus, wear behavior and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…For both samples group, films adhesion increased almost linearly according to the bias voltage increase during silicon interface deposition. Similar results of enhanced adhesion were also obtained by Ward 22 . When films adhesion is compared for each system, a much higher performance was observed for the samples grown in active screen system, as presented in Table 2.…”
supporting
confidence: 88%
“…For both samples group, films adhesion increased almost linearly according to the bias voltage increase during silicon interface deposition. Similar results of enhanced adhesion were also obtained by Ward 22 . When films adhesion is compared for each system, a much higher performance was observed for the samples grown in active screen system, as presented in Table 2.…”
supporting
confidence: 88%
“…values of both H/E and H 3 /E 2 (0.042 and 0.017 GPa respectively). The mechanical properties of the SS substrate are similar to that recorded by Ward et al[62] prior to coating with a-C:H with Si interlayer. The hardness of the HTS after hardening is similar to that seen by Wilbur et al[63] though a nitriding processing was used compared to the flame hardening for this study.…”
supporting
confidence: 79%
“…One of the reasons could be attributed to the diversity of the internal structure of GLC samples, where the sp 3 hybrid carbon atoms were commonly considered to be responsible for the high hardness and the rich sp 2 bond structure were reported to demonstrate an excellent wear resistance [13]. Deposition parameters such as target currents [10], substrate bias [14,15] and power densities [9,15,16], are the most common adjustable variables used to optimize the structure and properties of amorphous carbon films. For example, Wang et al [10] reported that the relative content of sp 2 and sp 3 hybridisation (ID/IG) changed from 1.5 to 3.0 with the increase of target current from 0.4 A to 2.0 A, while the hardness and film compactness decreased.…”
Section: Introductionmentioning
confidence: 99%